STUDI PADA PENGRAJIN SARUNG TENUN SAMARINDA - Fitriyani, Fitriyani; Ellyawati, Noor; Abu, Ilham; Sudarman, Sudarman; Reza, Reza; Riyadi, Riyo (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Micro, Small and Medium Enterprises is the main sector supporting the economy,therefore the sustainability of Micro, Small and Medium Enterprises is veryimportant. This study aims to find out how the woven sarong business is sustainablein Samarinda by looking at how innovation is, as well as the obstacles encounteredwhile running the business. This study uses descriptive qualitative research, bycollecting data through interviews with craftsmen or business owners of Samarindawoven sarongs. Data analysis techniques use data reduction, data display, anddrawing and verifying conclusions. Based on the results of interviews, it is knownthat the innovation of woven sarong craftsmen in the city of Samarinda is minimal.Products are only based on customer orders, especially in the production of clothing types. Product innovation is also influenced by circumstances such as the creation of woven masks. The most prominent innovation is related to design innovation, where craftsmen use trending young colors, this gets a positive response from customers. The constraints faced by craftsmen related to the production process are labor, health, time and weather and threads that often break. Barriers in terms of marketing are relatively minimal due to the lack of understanding of the craftsmen about the importance of marketing and the background of the existence of regular customers or resellers so that the craftsmen cannot be deceived. Craftsmen are expected to be even more innovative in terms of product design and novelty so that their businesses can grow and absorb labor and utilize technology as a marketingmedium.Keywords: Innovation, Marketing, SME, Weaving Sarong Craftsmen.